Assista outra vez: uma revisitação dos contos de fadas através de A Bela Adormecida (1959) e Malévola (2014) - Mazzini, Amanda Rosasco (2018)
The dissertation proposes a revisitation of the oral and literary fairy tales’ tradition that gave rise to the movies Sleeping Beauty (Clyde Geronimi, 1959) and Maleficent (Robert Stromberg, 2014), produced by Walt Disney Pictures. The objective is to make a historical retrospective of fairy tales’ origins, going through the medieval moment, through literature, painting, and comparing with the movies’ moment of mass communication. This path through the arts culminates in an analysis of each film, seeking its modes of address, the implications of the filmic text regarding the audience, and the artistic references prior to the movies. The main researchers of fairy tales used here are Bruno Bettelheim, Elizabeth Harries, Maria Cristina Martins, Vladimir Propp, Maria Tatar, Marina Warner and Jack Zipes. Gathering the connection between the films and the fairy tales’ tradition brings a different look at Disney, understanding to what extent the production company is a continuation of fairy tales’ canon.